Validation of a Non-linear Molecular Model of Polymer Creep - André, José Reinas (2004)
Previous models for the interpretation of the creep behaviour of polymers are of course valuable, but mainly empirical or semiempirical, and do not directly take into account the physical (molecular) underlying mechanisms, namely the detailed conformational and other transitions responsible for the material’s non-linear viscoelastic behaviour [1-10]. Any realistic and accurate model should predict and quantify the peculiar and coupled time-temperature-stress behaviour, and this is shown to be possible by adequate kinetic formulation of the frequencies (or retardation times) of the whole range of structural contributors to the material’s compliance. One should mention here the old but seminal work by Eyring et al. [11,12], which at least had the merit to suggest how one could physically and mathematically link the oldest, Voigt-Kelvin and other, phenomenological models to the actual non-linear physical behaviour at the molecular scale.